The Tardive Dyskinesia Impact Scale (TDIS), a novel patient-reported outcome measure in tardive dyskinesia: development and psychometric validation - Robert H. Farber; Donald E. Stull; Brooke Witherspoon; Christopher J. Evans; Charles Yonan; Morgan Bron; Rahul Dhanda; Eric Jen; Christopher O.’ Brien (Journal of Patient-Reported Outcomes, 2024)
Abstract Background Tardive dyskinesia (TD), a movement disorder in which patients experience abnormal involuntary movements, can have profound negative impacts on physical, cognitive, and psychosocial functioning. The Abnormal Involuntary Movement Scale (AIMS), a clinician-rated outcome, is considered the gold standard for evaluating treatment efficacy in TD clinical trials. However, it provides little information about the impacts of uncontrolled movements from a patient perspective and can be cumbersome to administer in clinical settings. The Tardive Dyskinesia Impact Scale (TDIS) was developed as a patient-reported outcome measure to fulfill the need for a disease-specific impact assessment in TD. The objective of the present study was to develop and evaluate the psychometric properties of the TDIS to determine whether it is fit-for-purpose to measure TD impact. Methods Data from qualitative studies and phase 3 trials of a VMAT2 inhibitor for the treatment of TD (KINECT3 and KINECT4) were used to determine the psychometric properties of the TDIS. Qualitative research included concept elicitation and cognitive debriefing interviews with TD patients and their caregivers in order to assess how well the TDIS captured key domains of TD impact. Quantitative analyses to examine the psychometric properties of the TDIS included assessing construct validity (factor structure, known groups, and predictive validity) and responsiveness to change. Results Qualitative results showed that the TDIS captures the key TD impacts reported by patients and caregivers and that the TDIS was interpreted as intended and relevant to patients’ experiences. Quantitative results found evidence of 2 underlying domains of the TDIS: physical and socioemotional (Comparative Fit Index > 0.9). Known groups and predictive validity indicated that, compared with the AIMS, the TDIS captures unique content (correlation between AIMS and TDIS = 0.2–0.28). The TDIS showed responsiveness to change in treatment, with TDIS scores improving over 48 weeks in the 2 phase 3 trials. Conclusions The TDIS captures relevant information about the impact of TD and is easily administered in a clinician’s office or patient’s home. It may be used longitudinally to show changes in TD burden over time. The TDIS complements the AIMS; using these assessments together provides a more holistic assessment of TD.